Peningkatan Pemahaman Kebudayaan Masyarakat Mekah Sebelum Islam Melalui Bahan Ajar Berbasis WEB Pada Peserta Didik - Maria, Anly; Ramdan, Muhamad Sahrul (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
This study discusses improving students' understanding of the culture of Mecca before Islam through web-based teaching materials in SKI lessons. SKI lessons play a significant role in building students' understanding. However, in reality, students lack understanding and are less active during learning because the learning process has not utilised teaching materials aligned with learning objectives. This is evidenced by the results of the Learning Objective Achievement Criteria, which only reached approximately 30% of the 33 students. Therefore, solutions are needed to improve this situation, one of which is the implementation of web-based teaching materials. The objective of this study is to describe the level of students' understanding of the material on the Culture of Mecca Society Before Islam before and after the implementation of web-based teaching materials. The method used was Classroom Action Research. Based on the results of the classroom action research conducted over two cycles, there was an increase in understanding in Cycle I to 64% with a satisfactory rating, followed by another increase in Cycle II to 100% with a good rating. It can be understood that there was an increase in understanding with a significance of 34% from the pre-cycle to cycle I and 36% from cycle I to cycle II. Therefore, overall, there was an increase in students' understanding with a significance of 70% from the pre-cycle to cycle II.  Keywords: Web-based Teaching Materials; Improved Understanding